Jusnaturalismo e direito natural - duas visões: José Pedro Galvão de Souza e Paulo Ferreira da Cunha - Aguiar, Gisele Pereira (2022)
In this work, we study some elements of Natural Law in the thoughts of two scholars: the Brazilian José Pedro Galvão de Sousa and the Portuguese Paulo Ferreira da Cunha, in order to draw approximations or distances between their works. Therefore, we will make a brief theoretical framework on the subject, and then an analysis of some texts from each of the aforementioned philosophers, to then compare their confluent and dissonant thoughts and thus offer our conclusions